Перспективи використання електричних апаратів в рамках концепції Smart Grid - Лупіков, В.С.; Болюх, В.Ф.; Байда, Є.І.; Крюкова, Н.В.; Варшамова, І.С.; Лелюк, М.А.; Литвиненко, В.В. (Технічна електродинаміка, 2012)
Analysis of the Smart Grid concept are resulted regarding of electric devices using . Primary tasks of electric devices development and their decision are formulated.